Economic Efficiency of Drip Irrigation System in Case of High-Value Crop Cultivation - Yedoyan, T. V. (ՀԱԱՀ հիմնադրամ)
In current conditions of significant reduction in underground water basin reserves in Ararat Valley, there is a need to introduce effective irrigation technologies and provide their economic justification. In this research paper it has been shown, that in case of surface irrigation of highvalue crops in Ararat Valley and its low-lying (irrigated) zone, 457.8 mln m3 water, and in case of drip irrigation – 171.7 mln m3 water is required. The total costs of introducing drip irrigation system in these fields ranges from AMD 742609-1995000, with a payback period of 1 to 1.5 years.
Keywords: Agricultural Engineering